2020
DOI: 10.1055/s-0040-1703419
|View full text |Cite
|
Sign up to set email alerts
|

Citation Classics on Dental Caries: A Systematic Review

Abstract: Objective A systematic search was performed for the identification and analysis of the 100 most often cited articles on dental caries and to highlight the changing trends in the field of dentistry over time. Materials and MethodsThe search was performed without any restriction on the study design, publication year, or language using the Web of Science (WoS) group of Clarivate Analytics enabling the search through "All Databases." Based on the citation count as available in WoS, the articles were sorted in a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
1
22
1
Order By: Relevance
“…In some fields, 100 or more citations of a publication are considered enough to classify it as a 'classic' [6]. In perspective, the article ranked as 100 th in the current study received 940 citations in comparison with the article ranked as 1 st in the field of homeopathy research that received 1172 citations [123] or with the article ranked as 1 st in the dental caries research that received 2003 citations [19]. For the current study, the publications receiving more than 400 citations can be considered classics.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In some fields, 100 or more citations of a publication are considered enough to classify it as a 'classic' [6]. In perspective, the article ranked as 100 th in the current study received 940 citations in comparison with the article ranked as 1 st in the field of homeopathy research that received 1172 citations [123] or with the article ranked as 1 st in the dental caries research that received 2003 citations [19]. For the current study, the publications receiving more than 400 citations can be considered classics.…”
Section: Discussionmentioning
confidence: 90%
“…The "Visualization of Similarities (VOS) viewer software" is widely to graphically illustrate the bibliometric parameters in mapping networks, which allow easy visualization of critical elements [2,[19][20][21]. The current study used VOS to represent a graphical mapping of keywords as identified bibliometric analysis to identify the focus of research in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…After the US, European countries, including the Netherlands and the UK, were prominent in this list of contributing authors. In addition to this study, several other bibliometric analyses reported that authors from Asia, Africa, and the Middle East, whether they were the first or the corresponding author, made a negligible contribution that could be considered a “classic” article [ 53 , 71 , 72 , 73 , 74 ]. Potential reasons might include language barriers, gaps in conducting research, and professional networking, as well as limited information access [ 75 ].…”
Section: Discussionmentioning
confidence: 67%
“…This significant contribution could be attributed to a larger scientific population, active researchers, and ample financial resources [ 46 , 53 , 72 , 74 , 76 , 77 , 78 , 79 ]. In addition to an unparalleled research work, an increased tendency among authors to cite articles originating from the US was observed [ 53 , 80 ]. It is noteworthy that first and second-ranked articles in the present study originated from the institutions hailing from Scandinavia, i.e., Norway and Denmark, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation